Cracking Culture: Exploration of Bugis Salted Eggs as a Chemistry Learning Resource - Yusaerah, Nur; Imranah, Imranah; Elvira, Elvira (Universitas Pendidikan Mandalika, 2025)
The traditional production of salted eggs in Soppeng Regency, South Sulawesi, reflects scientific principles relevant to chemistry education. This study explores this local practice through an ethnoscience perspective and assesses its potential as a contextual chemistry learning resource. A qualitative descriptive design with an ethnographic approach was used. Data were collected through observation, interviews, and documentation involving key informants (senior artisans), main informants (active producers), and supporting informants (community members). Data analysis applied source triangulation and inductive reasoning to ensure validity and allow themes to emerge. The findings reveal that the salted egg-making process incorporates various chemical concepts, including diffusion, osmosis, protein denaturation, physical and chemical changes, solution chemistry, and colligative properties. Artisans demonstrate empirical knowledge through consistent techniques, even without using formal scientific terms. The novelty of this study lies in its systematic integration of traditional salted egg production with core chemical concepts, positioning it as a culturally grounded and pedagogically valuable learning resource aligned with the Merdeka Curriculum. The practice embodies local values such as diligence, cooperation, and sustainability, making it suitable for character education and the Profil Pelajar Pancasila. Integrating this ethnoscientific knowledge into classroom instruction can help students grasp abstract chemistry concepts through real-life, culturally relevant contexts. Overall, this study supports the use of local wisdom as a means to enrich science education and preserve cultural heritage.